The Legal Regulations of Collateral Appeals in the Jordanian Shari’a Procedure Law No. (31) Of 1959 as Amended by Law No. (11) Of 2016: A Comparative Study - Soboh, Raed Lutfi Mahmoud (Dirasat: Shari'a and Law Sciences, 2023)
Objectives: This study sheds light on the collateral appeals submitted to the Jordanian Sharia Courts of Appeal in accordance with the Sharia Procedure Law. A collateral appeal gives the respondent the right to respond to the original appeal even after the expiry date of filing an appeal. Methods: The study uses the analytical approach to review the legal texts governing collateral appeals in the Sharia Procedure Code and to compare them with comparative law and jurisprudence. Results: The results show that the collateral appeal is an ordinary appeal by which the respondent responds to an appeal made by the appellant after the appeal’s deadline. The study also reveals that the collateral appeal either follows the usual procedures and general rules of the original appeal (whether it has been filed or not) or is filed with a written memorandum containing the reasons for the appeal. This process takes place within ten days following the date of notifying the respondent of the original appeal list. Conclusions: This study recommends that collateral appeals should be exempted from fees, whether they respond to original appeals or merely adhere to their rules.